MASORO: TRADISI TOLAK BALA MASYARAKAT SUKU BAJO TOROSIAJE - Tonny Iskandar Mondong; Owen Saleh (Universitas Negeri Gorontalo, 2021)
This research was conducted to reveal problems related to the Masoro tradition of the Bajo Tribe, to be precise in Bajo Village, Popayato District. This research was conducted using historical research methods through four stages of research in accordance with historical disciplines which include heuristics (source gathering), source criticism, interpretation (interpretation of sources) and historiography (history writing). This research method is used to thoroughly reveal the historical background and the meaning contained in the ritual tradition of rejecting reinforcements or what is known as the masoro tradition. In general, this tradition is carried out by the Bajo people to reject reinforcements. It is known that the ritual of countering reinforcements is not only carried out by the Bajo people, but the ritual is carried out by many ethnic groups who consider the ritual sacred and are believed to be able to keep the community away from all kinds of reinforcements, diseases, natural disasters and so on, one of the implementations in several areas is in the Petalang community who hold a ritual of rejecting reinforcements in anticipation of some disease or disaster caused by disturbances from spirits. However, this research will present in detail the tradition of rejecting reinforcements in the Bajo people.